A study on impact of affective commitment, continuance commitment and normative commitment on intention to quit among employees at Mahkota Hotel Melaka / Fatin Diyana Suriatuddin and Nurfatin Rosli - Suriatuddin, Fatin Diyana; Rosli, Nurfatin (Faculty of Business Management, 2016)
In this recent year, employees become the valuable asset and also are one of the crucial factors for organization to be success in this challenging world. However, as the economic fluctuates from the time to time, it is hard for employers to retain employees in an organization and to determine which factors would be the most influential for employees to quit from job. To this end, the main purpose of conducting this research project mainly is to examine the impact of affective commitment, continuance commitment, and normative commitment on intention to quit among employees at Mahkota Hotel Melaka. This study has been conducted in Mahkota Hotel Melaka using questionnaires as the research instrument in order to collect all the data from 140 respondents from different department. In this study, there are three independent variables which consist of the elements like affective, normative and continuance commitment meanwhile the independent variables is intention to quit. The methods used in data analysis for this study were descriptive analysis, reliability analysis, pearson correlation analysis and multiple regression analysis. The data collected then were analyzed and interpret using the Statistical Package for Social Science (SPSS) version 22. This study is beneficial in order to determine which organizational elements becomes the stronger predictor on employee’s intention to quit from organization. By identifying the key predictor of turnover intention among employees in organization, it can be serve as a guideline to help and enabled the employer in deciding the proper ways on how to reduce turnover rate and retain most of the capable employees in their organization. Finally, the research project also provides with clear view of limitations therefore brought forward some useful recommendations that will be beneficial to the organization itself.